2008
DOI: 10.1029/2007gl032009
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of very large amplitude whistler‐mode waves in Earth's radiation belts

Abstract: [1] During a passage through the Earth's dawn-side outer radiation belt, whistler-mode waves with amplitudes up to more than $240 mV/m were observed by the STEREO S/WAVES instrument. These waves are an order of magnitude larger than previously observed for whistlers in the radiation belt. Although the peak frequency is similar to whistler chorus, there are distinct differences from chorus, in addition to the larger amplitudes, including the lack of drift in frequency and the oblique propagation with a large lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
311
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 269 publications
(326 citation statements)
references
References 33 publications
15
311
0
Order By: Relevance
“…[28] Cattell et al [2008] have shown that very large amplitude, oblique whistlers can cause significant pitch-angle scattering and electron energization of high-energy test particle electrons on a time scale of ∼0.1 s. These simulations, based on those of Roth et al [1999], were run for this paper with conditions representative of the inner plasmasphere with the following results: resonant particles were seen to decrease their pitch angle by up to ∼20°and increase their energy by 25 keV in the same short time scale. Thus these whistler waves are able to pitch-angle scatter and energize electrons on a time scale orders of magnitude shorter than that of quasi-linear diffusion, the time-averaged manner in which small-amplitude whistler waves interact with electrons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Cattell et al [2008] have shown that very large amplitude, oblique whistlers can cause significant pitch-angle scattering and electron energization of high-energy test particle electrons on a time scale of ∼0.1 s. These simulations, based on those of Roth et al [1999], were run for this paper with conditions representative of the inner plasmasphere with the following results: resonant particles were seen to decrease their pitch angle by up to ∼20°and increase their energy by 25 keV in the same short time scale. Thus these whistler waves are able to pitch-angle scatter and energize electrons on a time scale orders of magnitude shorter than that of quasi-linear diffusion, the time-averaged manner in which small-amplitude whistler waves interact with electrons.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of STEREO burst memory data by Cattell et al [2008] led to the discovery of very large amplitude (>200 mV/m) whistler waves in the outer radiation belt. Wave-particle simulations suggested that these waves were sufficiently large in amplitude that they are able to strongly interact with highenergy electrons via nonlinear energization and pitch-angle scattering on a time scale of a single wave-electron encounter (∼0.1 s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEREO TDSMax, a once-per-minute record of the maximum high-frequency electric field, indicates that large amplitude waves were indeed present on all four crossings. The lack of burst captures then suggests that they were overwritten by later large amplitude waveforms, like the extremely large amplitude whistler mode waves reported by Cattell et al [2008], before they had a chance to be telemetered to the ground.…”
Section: Stereo and Wind Survey And Event Analysismentioning
confidence: 99%
“…They typically exhibit discrete rising or falling tones thought to originate from non-linear processes [4], but can also occur as wide-band incoherent hiss [5]. These chorus waves play a critical role in the acceleration of low-energy trapped radiation belt electrons to relativistic energies, and can also lead to rapid scattering loss into the atmosphere [6,7,8,9]. Previous attempts to remotely excite artificial whistler waves have been made in the Earth's near-space environment and have yielded interesting results [10,11], but have been difficult to probe and control.…”
Section: Introductionmentioning
confidence: 99%